2010
DOI: 10.1007/s11071-010-9654-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fetal cortical complexity from MR images using 3D entropy based information fractal dimension

Abstract: The fetal cortical complexity is a significant quantification for assessing the development of fetal brain. This study attempts to quantify the development of fetal cortical complexity using the concept of fractal dimension (FD) analysis. Thirty-two fetal MR images were selected from Taipei Veterans General Hospital at 27-37 weeks of gestational age (GA). To investigate the FD of fetal cortical complexity, the entropy based information fractal dimension method (FD EBI ), which is modified from Box-Counting met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These asymmetries may be indicators of cortical functional specialization [Dubois et al, 2008], and alterations of this pattern may be useful as an early biomarker for abnormal neurodevelopment [Studholme and Rousseau, 2014]. Using fractal dimension analysis in outer cortical surfaces reconstructed from 2D slices, Shyu et al, [2010] found earlier development of cortical complexity in the right hemisphere than in the left in a cohort of 32 fetuses with GA between 27 and 37 weeks. This was also reported in preterm [Dubois et al, 2008] and term [Hill et al, 2010] neonates, particularly evident at the level of the superior temporal sulcus.…”
Section: Interhemispheric Structural Asymmetriesmentioning
confidence: 94%
“…These asymmetries may be indicators of cortical functional specialization [Dubois et al, 2008], and alterations of this pattern may be useful as an early biomarker for abnormal neurodevelopment [Studholme and Rousseau, 2014]. Using fractal dimension analysis in outer cortical surfaces reconstructed from 2D slices, Shyu et al, [2010] found earlier development of cortical complexity in the right hemisphere than in the left in a cohort of 32 fetuses with GA between 27 and 37 weeks. This was also reported in preterm [Dubois et al, 2008] and term [Hill et al, 2010] neonates, particularly evident at the level of the superior temporal sulcus.…”
Section: Interhemispheric Structural Asymmetriesmentioning
confidence: 94%
“…Fractal dimension is an epoch-making development since it extends empirical dimension to nonintegral value. It is an important parameter describing fractal characteristic quantitatively, not only defined by value, but also calculated precisely by use of all sorts of software through experimental method [3,4]. Similar dimension is defined as D s =ln b / ln a, where a is what the graph is reduced 1/a, b is what b analogues form the graphics whole.…”
Section: The Box Dimension Definitionmentioning
confidence: 99%
“…Gyrification is considered a potential marker of early neurodevelopment since the formation of gyri and sulci in the brain begins between 10 and 15 weeks of human fetal life and reaches its peak during the third trimester of fetal life [ 27 ]. Conversely, FD increases from fetal life through childhood and into adulthood, until it starts to decrease later in life [ 27 , 28 , 29 ]. Interestingly, both GI and FD provide useful information on cognitive abilities due to their close relationship with innate intelligence and with developmental changes, respectively [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%